Dynamic Conditional Beta is Alive and Well in the Cross-Section of Daily Stock Returns - Turan G. Bali; Robert F. Engle; Yi Tang (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
This paper investigates the significance of dynamic conditional beta in predicting the cross-sectional variation in expected stock returns. The results indicate that the time-varying conditional beta is alive and well in the cross-section of daily stock returns. Portfolio-level analyses and firm-level cross-sectional regressions indicate a positive and significant relation between dynamic conditional beta and future returns on individual stocks. An investment strategy that goes long stocks in the highest conditional beta decile and shorts stocks in the lowest conditional beta decile produces average returns and alphas of 8% per annum. These results are robust to controls for size, book-tomarket, momentum, short-term reversal, liquidity, co-skewness, idiosyncratic volatility, and preference for lottery-like assets.
Keywords: G10; G11; C13; 330; dynamic conditional beta; conditional CAPM; ICAPM; and expected stock returns